The Semantics of word formation and lexicalization - Hacken, Pius ten; Thomas, Claire (Edinburgh Edinburgh University Press, 2013)
In this book, the focus is on the semantic aspect of the formation of new words rather than on generating the form as is more traditional. Each chapter concentrates on a specific question about a theoretical concept or a word formation process in a particular language and adopts a theoretical framework that is appropriate to the study of this question.
Word formation, meaning and lexicalization -- Semiproductivity and the place of word formation in grammar -- Lexicalization in generative morphology and conceptual structue -- Term formation in a special language -- Nominal compounds as naming devices -- Semantic and formal structure -- The semantics of lexical modification -- Semantic transparency and anaphoric islands -- Semantic coindexation -- Deverbal nominalizations in English -- Degrees of lexicalization in Ancient Greek deverbal nouns -- How many factors influence the meaning of denominal an deadjectival verbs? -- Analysing en- and its Romance equivalens in Jackenduff's conceptual structure -- Semantics of diminutivization.
Includes bibliographical references (pages 290-308) and indexes.
Keywords: Grammar, Comparative and general -- Word formation; Semantics